2021
DOI: 10.1016/j.asmr.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Opioid Prescription After Anterior Cruciate Ligament Reconstruction Does Not Affect Postoperative Pain or Prescription Refills: A Prospective, Surgeon-Blinded, Randomized, Controlled Trial

Abstract: Purpose: To investigate opioid utilization after anterior cruciate ligament (ACL) reconstruction in the setting of a multimodal pain regimen and assess the feasibility of prescribing fewer opioids to achieve adequate postoperative pain control. Methods: Patients undergoing ACL reconstruction in conjunction with a multimodal approach to pain control were randomized to receive either 30 or 60 tablets of hydrocodone (10 mg)eacetaminophen (325 mg). Patients were contacted at multiple time points up to 21 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…36,48 Furthermore, the reporting patterns of postoperative pain are likely influenced by increased pressure to develop standardized opioid prescription protocols as well as multimodal analgesic pathways. 17,20 The increasing prevalence of the 12-and 36-Item Short Form Health Surveys is reflective of the evolving recognition of the importance of physical, social, and emotional health in those with ACL injury and their influence on patient outcomes. 12 The heterogeneity observed with regard to PROs is not unique to ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…36,48 Furthermore, the reporting patterns of postoperative pain are likely influenced by increased pressure to develop standardized opioid prescription protocols as well as multimodal analgesic pathways. 17,20 The increasing prevalence of the 12-and 36-Item Short Form Health Surveys is reflective of the evolving recognition of the importance of physical, social, and emotional health in those with ACL injury and their influence on patient outcomes. 12 The heterogeneity observed with regard to PROs is not unique to ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid prescription following ACLR has been shown to be the greatest compared with other commonly performed sports medicine procedures. 13 , 15 , 20 Even so, a recent randomized controlled trial by Hartwell et al. 20 reported that in a pool of 85 patients undergoing ACLR, reduced opioid prescriptions do not affect postoperative pain or prescription refills.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 15 , 20 Even so, a recent randomized controlled trial by Hartwell et al. 20 reported that in a pool of 85 patients undergoing ACLR, reduced opioid prescriptions do not affect postoperative pain or prescription refills. Further, studies have shown that most patients stopped taking opioids by postoperative day 7 following ACLR, highlighting the building evidence that patients may require fewer opioids than is traditionally prescribed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent randomized trial, Moutzouros et al demonstrated equivalence in postoperative pain control when utilizing either a non-opioid multimodal pain control or a traditional opioid analgesic-based regimen after anterior cruciate ligament reconstruction (ACLR) 11 . Another study demonstrated equivalent opioid usage and postoperative pain scores when either 30 or 60 tablets of 10-mg hydrocodone plus 325-mg acetaminophen were prescribed, and suggested that 81% of patients could have had their pain medication requirements met with a 15-pill prescription 12 . However, the opioid-sparing trial did not address the usage of nonsteroidal anti-inflammatory drugs (NSAIDs) by the opioid-based treatment cohort, and neither of these trials offered a formal report or analysis of patient satisfaction with such interventions.…”
mentioning
confidence: 99%